PENERAPAN TEKNIK AVERSI DALAM MEMODIFIKASI PERILAKU MENYIMPANG MURID AUTIS KELAS DASAR IV DI SD INPRES MACCINI BARU MAKASSAR - Andhar wijaya; Usman Usman (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
This research aims to describe applying aversion techniques to modify the deviant behaviour of students with autism. This research method is single-subject experimental research with an A-B-A research design. The approach used was quantitative. The subjects were 10-year-old female students with autism who attend SD Inpres Maccini Baru Makassar. The source of the data obtained from observation, interviews, treatment and documentation techniques. The results showed that applying the aversion technique affected decreasing deviant behaviour of students with autism. These results indicated by the application of the aversion techniques in modifying deviant behaviour: 1) Baseline 1 (A1) stable with a percentage of 100%; 2) Intervention (B) stable with a percentage of 57, 75%; 3) Baseline 2 (A2) stable with a percentage of 40%; 4) Analysis between conditions did not occur overlapping data. It concluded that the aversion technique application reduces or even eliminate students' deviant behaviour with autism in grade IV of SD Inpres Maccini Baru Makassar.